A modified sub-block DDA fracturing modelling method for rock. (February 2020) - Ni, Kesong; Yang, Jun; Ning, Youjun; Kang, Ge
Abstract: Discontinuous deformation analysis (DDA) computes the mechanical behaviours of discrete deformable-block systems. It also has been used to simulate continuous rock fracturing, e.g., through the sub-block approach. In the present study, the sub-block DDA method is first verified in simulations of continua. The influences of the contact penalty spring stiffness and mesh size on the stress and strain calculations are investigated. Thereafter, the fracturing modelling algorithm of the sub-block DDA is improved, which determines the tensile or shear fracturing failure along artificial joints based on the stress state of adjacent sub-blocks according to the maximum tensile stress criterion and the Mohr–Coulomb criterion, respectively. The tensile, shear, mixed-mode, as well as dynamic fracturing failures of rock samples are simulated, and the results are calibrated theoretically or experimentally. Compared with former sub-block DDA fracturing modelling algorithms which determine the fracturing failure along artificial joints based on the contact stresses between sub-blocks, the improved algorithm has better accuracy in terms of the failure strength, and it significantly reduces the influence of the distribution of the pre-set artificial joints on the failure strength and fracturing route simulation results. This work makes DDA a better candidate for use in rock fracturing problem simulations.